Impact of dust deposition on PV performance and hotspot generation: I-V and thermal analysis with SEM and UV-VIS-NIR - Islam, Md. Imamul; Mohd Shawal, Jadin; Al Mansur, Ahmed (IEEE, 2024)
Dust accumulation on solar photovoltaic (PV) panels can significantly hinder their performance and promote the formation of hotspots. The present research aimed to explore the interplay between dust deposition, deterioration of panel output, and the emergence of hotspot regions in field-operated PV modules. Electrical characterization through I-V curve analysis revealed a decline in key parameters such as short-circuit current (Isc), open-circuit voltage (Voc), maximum power (Pmax), and fill factor (FF), indicating reduced performance attributable to dust accumulation. Thermal imaging inspections identified multiple localized hotspot areas coinciding with regions of substantial dust buildup on the panel surfaces. Spectroscopic analysis using UV-VIS-NIR techniques demonstrated that the dust exhibited strong ultraviolet light absorption, moderate absorption in the visible range around 450 nm wavelength, and relatively low absorption in the near-infrared region. Morphological examination through scanning electron microscopy (SEM) unveiled irregularly shaped dust particles with varying size distributions, while energy-dispersive X-ray spectroscopy (EDS) identified carbon, oxygen, aluminum, and silicon as major elemental constituents contributing to light absorption and scattering effects. The collective impact of these dust properties hindered efficient light transmission to the solar cells, culminating in diminished power generation capacity. This comprehensive investigation sheds light on the detrimental consequences of dust deposition on PV performance and hotspot formation, underscoring the necessity for implementing dust mitigation strategies to sustain optimal efficiency in solar power plants operating in dusty environments.